Detection of bacterial fluorescence from in vivo wound biofilms using a point‐of‐care fluorescence imaging device. Issue 5 (9th February 2021) - Lopez, Andrea J.; Jones, Laura M.; Reynolds, Landrye; Diaz, Rachel C.; George, Isaiah K.; Little, William; Fleming, Derek; D'souza, Anna; Rennie, Monique Y.; Rumbaugh, Kendra P.; Smith, Allie Clinton
Abstract: Wound biofilms must be identified to target disruption and bacterial eradication but are challenging to detect with standard clinical assessment. This study tested whether bacterial fluorescence imaging could detect porphyrin‐producing bacteria within a biofilm using well‐established in vivo models. Mouse wounds were inoculated on Day 0 with planktonic bacteria (n = 39, porphyrin‐producing and non‐porphyrin‐producing species, 10 7 colony forming units (CFU)/wound) or with polymicrobial biofilms (n = 16, 3 biofilms per mouse, each with 1:1:1 parts Staphylococcus aureus/Escherichia coli/Enterobacter cloacae, 10 7 CFU/biofilm) that were grown in vitro . Mouse wounds inoculated with biofilm underwent fluorescence imaging up to Day 4 or 5. Wounds were then excised and sent for microbiological analysis. Bacteria‐matrix interaction was assessed with scanning electron microscopy (SEM) and histopathology. A total of 48 hours after inoculation with planktonic bacteria or biofilm, red fluorescence was readily detected in wounds; red fluorescence intensified up to Day 4. Red fluorescence from biofilms persisted in excised wound tissue post‐wash. SEM and histopathology confirmed bacteria‐matrix interaction. This pre‐clinical study is the first to demonstrate the fluorescence detection of bacterial biofilm in vivo using a point‐of‐care wound imaging device. These findings have implications for clinicians targeting biofilm and may facilitate improved visualisation and removal of biofilms.